Cellugyrin (synaptogyrin-2) dependent pathways are used by bacterial cytolethal distending toxin and SARS-CoV-2 virus to gain cell entry - Kathleen Boesze-Battaglia; Gary H. Cohen; Paul F. Bates; Lisa M. Walker; Ali Zekavat; Bruce J. Shenker (Frontiers in Cellular and Infection Microbiology, 2024)
Aggregatibacter actinomycetemcomitans cytolethal distending toxin (Cdt) is capable of intoxicating lymphocytes macrophages, mast cells and epithelial cells. Following Cdt binding to cholesterol, in the region of membrane lipid rafts, the CdtB and CdtC subunits are internalized and traffic to intracellular compartments. These events are dependent upon, cellugyrin, a critical component of synaptic like microvesicles (SLMVCg+). Target cells, such as Jurkat cells, rendered unable to express cellugyrin are resistant to Cdt-induced toxicity. Similar to Cdt, SARS-CoV-2 entry into host cells is initiated by binding to cell surface receptors, ACE-2, also associated with cholesterol-rich lipid rafts; this association leads to fusion and/or endocytosis of viral and host cell membranes and intracellular trafficking. The similarity in internalization pathways for both Cdt and SARS-CoV-2 led us to consider the possibility that cellugyrin was a critical component in both processes. Cellugyrin deficient Calu-3 cells (Calu-3Cg-) were prepared using Lentiviral particles containing shRNA; these cells were resistant to infection by VSV/SARS-CoV-2-spike pseudotype virus and partially resistant to VSV/VSV-G pseudotype virus. Synthetic peptides representing various regions of the cellugyrin protein were prepared and assessed for their ability to bind to Cdt subunits using surface plasmon resonance. Cdt was capable of binding to a region designated the middle outer loop (MOL) which corresponds to a region extending into the cytoplasmic surface of the SLMVCg+. SARS-CoV-2 spike proteins were assessed for their ability to bind to cellugyrin peptides; SARS-CoV-2 full length spike protein preferentially binds to a region within the SLMVCg+ lumen, designated intraluminal loop 1A. SARS-CoV-2-spike protein domain S1, which contains the receptor binding domains, binds to cellugyrin N-terminus which extends out from the cytoplasmic surface of SLMV. Binding specificity was further analyzed using cellugyrin scrambled peptide mutants. We propose that SLMVCg+ represent a component of a common pathway that facilitates pathogen and/or pathogen-derived toxins to gain host cell entry.